PCR Method To Identify Salmonella enterica Serovars Typhi, Paratyphi A, and Paratyphi B among Salmonella Isolates from the Blood of Patients with Clinical Enteric Fever - Levy, Haim (American Society for Microbiology (ASM), 2008)
PCR methodology was developed to identify Salmonella enterica serovars Typhi, Paratyphi A, and Paratyphi B. One multiplex PCR identifies serogroup D, A, and B and Vi-positive strains; another confirms flagellar antigen “d,” “a,” or “b.” Blinded testing of 664 Malian and Chilean Salmonella blood isolates demonstrated 100% sensitivity and specificity.